2006
DOI: 10.1002/bit.20876
|View full text |Cite
|
Sign up to set email alerts
|

Transient performance of two‐phase partitioning bioreactors treating a toluene contaminated gas stream

Abstract: Two-phase partitioning bioreactors (TPPBs) consist of a cell-containing aqueous phase and an immiscible organic phase that sequesters and delivers toxic substrates to cells based on equilibrium partitioning. The immiscible organic phase, which acts as a buffer for inhibitory substrate loadings, makes it possible for TPPBs to handle high volatile organic compound (VOC) loadings, and in this study the performance of liquid n-hexadecane and solid styrene butadiene (SB) polymer beads used as partitioning phases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…Similar observations on biomass have been made by Nielsen et al, 11 who reported an adaptation in biomass steady state when a benzene loading step change was imposed, suggesting evidence of a characteristic value of maintenance energy requirements. Boudreau and Daugulis 35 also found a constant cell concentration between 6.4 and 8.7 g L −1 in a TPPB with a solvent or polymer beads as the second phase.…”
Section: Growth and Cellular Viabilitymentioning
confidence: 92%
“…Similar observations on biomass have been made by Nielsen et al, 11 who reported an adaptation in biomass steady state when a benzene loading step change was imposed, suggesting evidence of a characteristic value of maintenance energy requirements. Boudreau and Daugulis 35 also found a constant cell concentration between 6.4 and 8.7 g L −1 in a TPPB with a solvent or polymer beads as the second phase.…”
Section: Growth and Cellular Viabilitymentioning
confidence: 92%
“…1 These reactors involve the use of a second non-aqueous phase ('oil') to improve the solubility and transfer of hydrophobic compounds. Some authors have proposed this technology as a way of removing hydrophobic compounds such as benzene, 2 hexane 3 and toluene, 4,5 and have demonstrated an improvement of elimination capacity in comparison with classical biofilters treating the same or similar compounds 6 -8 in terms of hydrophobicity. 9 In particular, the effectiveness of an aqueous-silicone oil (10% V/V) TPPB using Rhodococcus erythropolis T902.1 in removing volatile organic compounds (VOCs) from gaseous effluents has been established.…”
Section: Introductionmentioning
confidence: 99%
“…For shock-loads tested in the presence of the second organicphase by different researchers, an enhancement in the performance arising from the presence of a second-phase was observed. Anew, the instantaneous removal effi ciency recovery times, after re-instating pre-shock conditions, also show a clear trend with the one-liquid-phase system recovering more rapidly, as a result of little pollutant absorption (Boudreau and Daugulis 2006 ) .…”
Section: Suspended-growth Bioreactor Response To Transient Operationsmentioning
confidence: 94%